Phytosomes: A promising delivery system for anticancer agents by using phytochemicals in cancer therapy: Phytosomes as anticancer agents - Pooja Dave; Rupal Jani; G S Chakraborthy; Kaushal J Jani; Vijay Upadhye; Kahrizi, Danial; Ahmad Mir, Mushtaq; Siddiqui, Samra; Saeed, Mohd; Tarun Kumar Upadhyay (Cellular and Molecular Biology, 2023)
Plant extracts have been shown to be effective in treating a variety of ailments; however their hydrophilic nature and unique chemical structure have caused significant hurdles due to their low bioavailability. Phytosomes technology is used to improve the absorption of phytoconstituents that are difficult to absorb. Among the leading deaths in the society is malignancy. The aforementioned consumes remained a big issue for modern chemotherapy since it has yet to be treated in an efficient manner. The goal of this study is to outline the most recent research on the potential use of phytosome complexes for cancer therapy, as well as the formulation processes and mechanism of transportation through phytosomes.Nanotechnology has paved the way for cancer therapy by altering key features of medications and their carriers. Novel drug delivery systems are used to transfer antitumor drugs to the particular site via different nanostructures. Among several unique drug delivery systems, phytosomes are a creative way to transfer phytoactive compounds to the site of action, and several phytosomes formulations are now being used in clinical settings. Phytoconstituents’ anti-cancer activities are increased by phytosomal formulations.